2019
DOI: 10.1111/gtc.12727
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein receptor‐related protein 6 is required to maintain intercalated disk integrity

Abstract: The intercalated disk (ID), a highly organized adhesion structure connecting neighboring cardiomyocytes, fulfills mechanical and electrical signaling communication to ensure normal heart function. Lipoprotein receptor‐related protein 6 (LRP6) is a co‐receptor inducing canonical Wnt/β‐catenin signaling. It was recently reported that LRP6 deficiency in cardiomyocytes predisposes to arrhythmia independent of Wnt signaling. However, whether LRP6 directly regulates the structure of IDs requires further investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Mutations in LRP6 relate to early onset hypercholesterolemia, atherosclerosis, and osteoporosis in human [ 8 , 9 ]. We also observed LRP6 is a critical protein in intercalated disc (ID) and regulates the components of IDs [ 10 ]. In Li J’s work that LRP6 acts as a scaffold protein in cardiac gap junction assembly [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in LRP6 relate to early onset hypercholesterolemia, atherosclerosis, and osteoporosis in human [ 8 , 9 ]. We also observed LRP6 is a critical protein in intercalated disc (ID) and regulates the components of IDs [ 10 ]. In Li J’s work that LRP6 acts as a scaffold protein in cardiac gap junction assembly [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many studies demonstrated that Wnt signaling was linked to cardiac fibrosis which could impede electrical wave propagation and potentially cause arrhythmias (38)(39)(40). Furthermore, a recent study reported that LRP6 played an important role in keeping the integrity of the intercalated disk, on which the coordinated excitation and contractile performance of the myocardium were dependent, and the interaction between LRP6 and connexin43 might be involved in this process (41). Therefore, LRP6 variants might cause malignant arrhythmias and SCD via disturbing Wnt signaling pathways, as well as disrupting the function of gap junction and the intercalated disk of the myocardium.…”
Section: Lrp6 and Sudden Cardiac Deathmentioning
confidence: 99%